Shouting at the rain - Hunt, Lynda Mullaly (New York : Nancy Paulsen Books, 2019)
Delsie loves tracking the weather, living with her grandmother, and the support of friends and neighbors, but misses having a "regular family," especially after her best friend outgrows her.
Keywords: Grandmothers -- Fiction; Family life -- Massachusetts -- Cape Cod -- Fiction; Friendship -- Fiction; Neighborliness -- Fiction; Weather -- Fiction; JUVENILE FICTION / Family / Parents; JUVENILE FICTION / Social Issues / Drugs, Alcohol, Substance Abuse; JUVENILE FICTION / Social Issues / Emotions & Feelings; Cape Cod (Mass.) -- Fiction